Detection of SQL Injection Attack Using Machine Learning Techniques (International Journal of Scientific Research in Science and Technology, 2024)
SQL injection attacks (SQLIAs) remain a prevalent threat to web applications, exploiting vulnerabilities in database interactions to compromise data security. Detecting such attacks effectively is crucial for ensuring robust application security. This study investigates the use of machine learning techniques to identify SQLIAs by analyzing patterns and features in SQL queries. A dataset comprising both legitimate and malicious SQL queries is utilized to train and evaluate various machine learning models, including decision trees, support vector machines, and neural networks. The proposed approach achieves high accuracy in distinguishing between benign and malicious queries, showcasing the potential of machine learning for proactive SQLIA detection. The findings highlight the importance of feature selection, algorithm choice, and real-time detection capabilities in mitigating the risk of SQL injection attacks. This research provides a foundation for developing intelligent, automated systems to enhance the security of database-driven applications.